Pharmacological History of Missing Subjects: Perspective of a Correction Factor to Aid in the Study of Bone Remains - Cecannecchia, Camilla; Baldari, Benedetta; Cioffi, Andrea (Biology (Basel, Switzerland), 2022)
In forensic anthropology, bone mineral density and the estimation of the dating of fractures based on the degree of progress of healing processes are important parameters of study on bone remains. With our article we aim, on the one hand, to highlight the importance that these parameters have in the reconstruction of the biological profile of the subject, as well as the time and the cause of death; on the other hand, we aim to limit their variability according to the medical substances and/or abuse assumed during life by the subject. The aim of this article is to encourage the introduction of the pharmacological history of missing persons as a new correction factor for the study of bone remains, possibly based on new scientific studies that allow us to establish with greater specificity the effect that certain pharmacological therapies produce on bone mass and the speed of remodeling.